Drug-induced Myopia and Bilateral Angle Closure Secondary to Zolmitriptan. Issue 10 (October 2017) - Lee, Jonathan Tak Loong; Skalicky, Simon Edward; Lin, Ming-Lee
Abstract : Purpose: To describe a unique case of drug-induced transient myopia with angle-closure glaucoma in a patient being treated with zolmitriptan for migraines. Methods: A 42-year-old woman who had been using increasing amounts of zolmitriptan over the previous 12 months presented with an acute myopic shift and raised intraocular pressures (IOP) with anterior chamber shallowing. Clinical examination findings at presentation and at follow-up visits were reviewed. Results: Initial examination revealed unaided visual acuities of 20/100 in the right eye and 20/125 in the left, with IOP measuring 34 mm Hg bilaterally. Zolmitriptan was ceased and the patient was commenced on topical antiglaucoma medication. Within 2 weeks, IOP had normalized, with deepening of the anterior chambers and complete resolution of her myopia. Her final recorded unaided visual acuities were 20/12.5 in the right eye and 20/16 in the left. When topical antiglaucoma medication was ceased the patient developed pressure-related headaches and selective laser trabeculoplasty was performed to minimize the need for long-term topical medication use. Conclusion: Idiosyncratic drug reactions resulting in ciliochoroidal effusion, secondary angle closure, and transient myopia are well described, but they have not been previously reported with zolmitriptan use. An awareness of the various potential causative agents is important, as findings are generally reversible if recognized early and if the offending drug is discontinued.